Multivariate calibration of fourier transform infrared spectra in predicting anti-diabetic activity of momordica charantia fruit - Perumal, Vikneswari; Khatib, Alfi; Uzir, Bisha Fathamah; Abas, Faridah; Bajrai, Aishah; Ahmed, Qamar Uddin; Nik Yusoff, Nik Mohd. Idris (2014)
Momordica charantia or bitter melon is widely used as traditional medicine for diabetic patient. This study developed a statistical model in predicting the alpha-glucosidase inhibitory activity of M. charantia fruit based on Fourier Transform Infrared Spectroscopy (FTIR). A total of six different ethanol extracts (0, 20, 40, 60, 80, and 100%) of this plant were prepared. The chemical profiles of the extracts was conducted using FTIR spectroscopy between 4000 and 600/cm at a resolution of 4/cm. Multivariate Data Analysis (MVDA) was developed by correlating the bioactivity and the third derivative FTIR spectra of each individual extract using Orthogonal Partial Least Square (OPLS). The result revealed that the regression coefficient (R2) between actual and predicted α-glucosidase inhibitory activity was high (>0.80), and the standard error of prediction (SEP) and standard error of estimation (SEE) were acceptable. In conclusion, FTIR spectroscopy is a cheap and high-throughput technique that can be used as to predict the α-glucosidase inhibition activity of M. charantia fruit .